Comprehensive reproductive health care services during COVID19 in Nepal: An ethical analysis through Reproductive Justice Framework (Health Prospect, 2022)
Reproductive health care services are fundamental human rights of every individual, which are also stated by various international instruments. Nepal is also part of these international commitments and has reflected its commitment in the nation’s plan, strategy, and programs. Though significant efforts have been made to fulfill and improve the sexual and reproductive health care services in Nepal, women and marginalized communities are still deprived of the services. During the COVID-19 pandemic, the utilization of reproductive health services declined which is aggravating the situation and threatening to reverse the progress made so far. The article reviews the accessibility of comprehensive reproductive health services through the framework of reproductive justice during the COVID-19 in Nepal. Reproductive Justice is not only a framework for liberty for marginalized communities but also ethical guidance for policymakers and service providers.